Effect of Curvature Shape on the Impact Strength of Additively Manufactured Acrylonitrile Butadiene Styrene Parts Produced via Fused Deposition Modeling - Muhammad Fahad; Waseem Raja; Muhammad Naveed Iqbal; Abdul Waheed Awan (Designs)
Additive manufacturing (AM) has greatly revolutionized manufacturing due to its ability to manufacture complex shapes without the need for additional tooling. Most AM applications are based on geometries comprising curved shapes subjected to impact loads. The main focus of this study was on investigating the influence of infill density and the radius of curvature on the impact strength of parts manufactured via an FDM process. Standard geometrical specimens with varying part infill densities and radii of curvature were produced and subjected to Charpy impact tests to evaluate their impact strength. The results suggest that the impact strength increases with the increased density caused by higher amounts of material as well as by the changing cross-sectional areas of the beads. Also, the radius of curvature of the parts shows a clear inverse relationship with the impact energy absorbed by the specimens (i.e., increasing the radius decreased the impact energy of the parts) produced via an FDM process, which can be explained using the beam theory of structural mechanics. The maximum value of impact strength obtained was 287 KJ/m2, and this was achieved at the highest infill density (i.e., solid) and for the smallest radius of curvature.